2022
DOI: 10.1038/s41598-022-15443-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis on the association between ambient air pollution and pulmonary tuberculosis

Abstract: There is inconclusive evidence on the association between ambient air pollution and pulmonary tuberculosis (PTB) incidence, tuberculosis-related hospital admission and mortality. This review aimed to assess the extent to which selected air pollutants are associated to PTB incidence, hospital admissions and mortality. This was a systematic review of studies published in English from January 1st, 1946, through May 31st, 2022, that quantitatively assessed the association between PM2.5, PM10, NO2, SO2, CO, O3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…For example, Kun et al’s study showed that chronic exposure to PM 10 , nitrogen dioxide, and sulfur dioxide promoted the development of TB, whereas the relationship between PM 2.5 , ozone, and nitrous oxide and the development of TB was not so precise [ 24 ]. Dimala et al used a random effects model to investigate the relationship between PM 2.5 , PM 10 , CO, sulfur dioxide, nitrogen dioxide, and ozone and the incidence of TB, and their results indicated that the first three pollutants were positively associated with the incidence of TB, while the last three were not associated with the incidence of TB [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kun et al’s study showed that chronic exposure to PM 10 , nitrogen dioxide, and sulfur dioxide promoted the development of TB, whereas the relationship between PM 2.5 , ozone, and nitrous oxide and the development of TB was not so precise [ 24 ]. Dimala et al used a random effects model to investigate the relationship between PM 2.5 , PM 10 , CO, sulfur dioxide, nitrogen dioxide, and ozone and the incidence of TB, and their results indicated that the first three pollutants were positively associated with the incidence of TB, while the last three were not associated with the incidence of TB [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have linked ambient air pollution to poor TB outcomes. A recent meta-analysis including 24 studies determined that multiple air pollutants were associated with active TB [49]. Every 10 μg/m 3 increase in air pollutant concentration increased the risk for active TB incidence: for PM 2.5 , pooled aRR = 1.12 (95% CI, 1.06–1.19); for PM 10 , pooled aRR = 1.06 (95% CI, 1.01–1.12); and for sulfur dioxide, pooled aRR = 1.08 (95% CI, 1.04–1.12).…”
Section: Epidemiologymentioning
confidence: 99%
“…This paper describes the design of a patient-oriented pilot study which seeks to uncover the association between environmental heavy metals and TB. The rationale for the proposed study builds on existing research, highlighting that exposure to PM is significantly associated with an increased incidence of pulmonary TB (PTB) in adults 12. However, the current body of evidence is limited on the environmental risks for children in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for the proposed study builds on existing research, highlighting that exposure to PM is significantly associated with an increased incidence of pulmonary TB (PTB) in adults. 12 However, the current body of evidence is limited on the environmental risks for children in Bangladesh. Furthermore, significantly greater progress is required to achieve the UN Sustainable Development Goal, target 3.3, to end TB epidemics by 2030.…”
Section: Introductionmentioning
confidence: 99%